An Assessment of the knowledge of nurses working in pediatric wards regarding the concept of - Farideh Bastani (Iran University of Medical Sciences, 1999)
The research is a descriptive analytic study for assessing the knowledge of nurses, working in pediatric wards   regarding the concept of• Child Abuse in Tehran.   A total of 100 pediatric nurses who worked in general and sick-children hospitals were chosen randomly   and participated in this study. Data collection was performed with a questionnaire . The tool was a two part   questionnaire with the first part including demographic characteristics of the subjects, like age, .sex. marriage,   past experience in nursing and experience on children units. The second pan posed questions regarding the   assessment of knowledge towards the concept of child abuse", The procedures used for data analysis were   percentage of absolute and relative frequency, chi-square test, and pearson coefficient of correlation .   The results of this study showed that, there are significant differences between high level of awarenes of   surveyed nurses and level of their eduction more than B Sc. degree . passing short- period education regarding   the research matter and the acquiring information from mass- media and academic education in nursing . On the   other hand . there is no relationship between the nurses knowledge about child abuse problem and factors such   as: age, marriage situation, and job records in pediatric units , The overall findings revealed that the nurses   awareness rate in most of the cases (49%) were medium and in least of the cases (23%) were low and in 28%   of the participants were high in relation to the final goal Based on die findings , suggestions for further research and implementation of the findings in different areas of practice were made .